Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS Dengan Metode Problem Solving - Irwan Hariawan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to improve the critical thinking skills of class IX A SMPN 1 Warunggunung students in social studies learning by using the Problem Solving method. The type of research is Classroom Action Research (CAR). This action research was carried out in three cycles in which each cycle contained four components, namely plans, actions, observations, and reflections. The results of this study indicate that the application of the Problem Solving method can improve learning activities and student learning outcomes of class IX A SMPN 1 Warunggunung. This can be seen from the percentage of student learning activities in the first cycle of 47.73%, an increase of 18.87% in the second cycle to 66.60%, and an increase of 15.54% in the third cycle to 82.14%. Student learning outcomes in the first cycle of 65.97 experienced an increase of 12.36 in the second cycle to 78.33, and increased back to 9.29 in the third cycle to 87.62. Likewise, the percentage of mastery learning has increased from 46.62% in the first cycle, increased by 16.65% to 63.27% in the second cycle, then increased again 26.64% to 89.91% in the third cycle.